Population dynamics of Bemisia tabaci (Homoptera: Aleyrodidae) parasitoids on cassava mosaic disease resistant and susceptible varieties - Otim, M.; Legg, D.J.; Kyamanywa, S.; Polaszek, A.; Gerling, D. (Informa UK Limited, 2006)
Three field trials were conducted at Namulonge Agricultural and Animal Production Research Institute to investigate the population dynamics of Bemisia tabaci Gennadius and its associated aphelinid parasitoids in Uganda. Results showed that more whitefly occurred on the cassava mosaic disease-resistant variety, (Nase 4) compared to the susceptible variety, (Ebwanatereka). Two species of aphelinid parasitoids, Eretmocerus mundus Mercet and Encarsia sophia Girault and Dodd, were identified during the study. Overall percent parasitism did not differ significantly (P>0.05) between varieties in all the trials, but significant differences occurred at 13, 15 and 21 weeks after planting during late season (2000), 18 weeks after planting during early season (2001), and 8 weeks after planting during late season (2001). The trends in the build up in numbers of both parasitoids species and apparent parasitism were similar, differed significantly on certain dates. It was, however, noted that percent parasitism decreased with nymph number. The significance of this phenomenon on the potential use of these aphelinid parasitoids as biocontrol agents of the cassava whitefly is discussed.